2018
DOI: 10.1097/mlr.0000000000000915
|View full text |Cite
|
Sign up to set email alerts
|

Homeless Status, Postdischarge Health Care Utilization, and Readmission After Surgery

Abstract: Readmissions are higher in homeless individuals discharged to the community after surgery. Judicious use of postoperative nursing or residential rehabilitation programs may be effective in reducing readmission and improving care transitions among these vulnerable Veterans. Relative costs and benefits of alternatives to community discharge merit investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 21 publications
1
48
1
Order By: Relevance
“…13 Another recent study of veterans discharged from the hospital after surgical procedures, which included 5068 homeless patients, found a 43% higher odds of readmission to the hospital associated with homelessness. 14 We observed a smaller absolute difference in the readmission rates between the homeless and housed groups compared with some of these prior studies. Although differences in the definition of homelessness, statistical methods, and smaller sample sizes of those studies make direct comparisons difficult, our findings are concordant in that they demonstrated a significantly higher readmission rate associated with homelessness.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…13 Another recent study of veterans discharged from the hospital after surgical procedures, which included 5068 homeless patients, found a 43% higher odds of readmission to the hospital associated with homelessness. 14 We observed a smaller absolute difference in the readmission rates between the homeless and housed groups compared with some of these prior studies. Although differences in the definition of homelessness, statistical methods, and smaller sample sizes of those studies make direct comparisons difficult, our findings are concordant in that they demonstrated a significantly higher readmission rate associated with homelessness.…”
Section: Discussioncontrasting
confidence: 54%
“…Prior studies suggest that homeless individuals may experience higher rates of readmission after an index hospitalization. [12][13][14] However, these studies have been limited by a relatively small sample size of patients J Gen Intern Med 35 (9):2576-83 experiencing homelessness or have only evaluated certain medical conditions or procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] As a result, outcomes after hospital discharge may be poor, and studies in the USA have shown that homeless inpatients are more likely to be readmitted than housed inpatients. [12][13][14][15] In response to concerns about poor discharge arrangements for homeless inpatients, the UK government set up the 'Homeless Hospital Discharge Fund', 16 which funded partnerships of National Health Service (NHS) and non-profit organisations to develop methods of supported discharge. These schemes operated between 2013 and 2016 and used a range of models.…”
Section: Introductionmentioning
confidence: 99%
“…11 Titan et al looked at surgeries that occurred within the Veterans Health Administration and found that patients without housing were more likely to be readmitted postoperatively as compared with those individuals who had housing. 12 Patients residing in vulnerable communities have a markedly increased risk for serious postoperative complications, which increased relative to social vulnerability in a linear fashion. 13 The impact of social vulnerability was more evident in Black/minority patients, with an increased risk of mortality among Black patients across several surgical procedures and consistently higher than White patients.…”
Section: Current Situationmentioning
confidence: 99%